The Use of Contingency Theory in Management and Accounting Research - Ismail, Kamisah; Zainuddin, Suria; Sapiei, Noor Sharoja (Asian Journal of Accounting Perspectives, 2010)
Contingency theory has been widely accepted and used in management and accounting literature. It works based on the principle that the appropriateness of managerial techniques or systems is contingent upon the setting of that organisation. Contextual factors may explain the reasons for different systems that suit different organisations differently. This paper discusses the effect of the contextual factors (external environment, technology, structure, culture, size, and strategies) that may affect the organisation’s structure, and, consequently, affect the design of the accounting information system.